The Impact of ESG Disclosure on Stock Performance with Growth Opportunities as a Mediating Variable: Evidence from Indonesia’s Industrial Sector - Simbolon, Erpina; Patayoan, Abraham; Tansuria, Billy Ivan (Dinasti Publisher, 2026)
This study aims to examine the impact of ESG disclosure on stock performance in the Indonesian capital market, while highlighting the mediating role of growth opportunities. The research addresses the ongoing debate on whether ESG practices are fully recognized by investors in emerging markets, particularly Indonesia, where short-term profit orientation still dominates investment behaviour. The study adopts a quantitative research design was employed using secondary data obtained from annual and sustainability reports of companies listed on the Indonesia Stock Exchange. ESG disclosure was measured through content analysis based on the Global Reporting Initiative (GRI) indicators and OJK/IDX sustainability reporting guidelines. Stock performance was assessed through market-based indicators, while growth opportunities were proxied using price-to-book value ratio. The relationships among variables were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), including direct and indirect effect testing through mediation analysis. The empirical results show that ESG disclosure has no significant effect on either growth opportunities or stock performance, as reflected in the very low T-statistics and high p-values obtained in the structural model. Conversely, growth opportunities display a significant positive relationship with stock performance; however, this direct effect does not translate into a mediating influence. Mediation analysis confirms that the indirect path from ESG disclosure to stock performance through growth opportunities is statistically insignificant, indicating that growth opportunities do not function as a mediator. Taken together, these findings suggest that ESG disclosure does not yet serve as a credible or influential signal capable of shaping growth expectations or driving market valuation within the Indonesian capital market. This study contributes to the ESG literature by demonstrating that, despite global trends emphasizing the financial relevance of sustainability practices, the Indonesian market has not yet fully integrated ESG information into investment evaluations. The findings provide important implications for regulators, companies, and investors regarding the need to strengthen ESG reporting quality, improve investor literacy on sustainability issues, and develop policies that encourage the strategic adoption of ESG practices.